Composite electronic organ / Norhasnani Norani and Sarina Mohamed Isa - Norani, Norhasnani; Mohamed Isa, Sarina (2002)
This project is composite Electronic Organ. Keeping in view the high costs and functional limitations of most commercially available electronic musical organs, this lowest cost, yet full featured eleven octave electronic organ. It is use for musical like as piano and suitable for children and adults. The organ is based on the chromatic scale, the modified diatonic with semitones. In practice, the notes played on the keyboard switches, SI-SI 2 and S14 is used to shift from one octave to the next. Playing music on this keyboard is like typing with a typewriter having an unusual keyboard.